Impact of Metformin therapy on miR-9, miR-223, and miR-132 and inflammasome-related gen expression in obese and non-obes PCOS patients: A comparative study with healthy controls - Seyed Alireza Mirjalili; Seyed Mehdi Kalantar; Fateme Montazeri; Reyhaneh Azizi; Elham Hosseini; Fateme Zare; Samira Asgharzade; Korosh Ashrafi Dehkordi (PLoS ONE, 2025)
Introduction Polycystic Ovary Syndrome (PCOS) is a common endocrine and metabolic disorder characterized by chronic inflammation, insulin resistance, and hormonal imbalances, often leading to infertility and metabolic dysfunction. Metformin, an insulin-sensitizing agent, has shown potential to improve these conditions. This study investigated the impact of metformin on inflammasome-regulating microRNAs ( miR-9, miR-223, miR-132 ) and related genes ( IL-1β, IL-18, caspase-1, NLRP3 ) in obese and non-obese PCOS patients compared to healthy controls. Materials and methods In this case-control study, 100 women aged 18–35 were divided into 50 PCOS patients and 50 controls, stratified by BMI (>25 kg/m² and <25 kg/m²). Blood samples were analyzed pre- and post-12 weeks of metformin treatment (500 mg twice daily) for serum hormone levels (FSH, LH, TSH) by ELISA kit, miRNA and mRNA expression by qPCR, and follicle count by transvaginal ultrasound were evaluated. Results The results demonstrated a significantly lower expression of miR-9 in PCOS patients (BMI >25 kg/m²) compared to healthy controls (mean ± SD: 0.54 ± 0.07 vs. 1.00 ± 0.11; P < 0.001). Following metformin treatment, miR-223 expression was significantly upregulated (from 0.88 ± 0.06 to 1.21 ± 0.08; P = 0.002). Similarly, the expression levels of IL-1β (2.01 ± 0.31 vs. 1.31 ± 0.23) and NLRP3 (2.12 ± 0.27 vs. 1.38 ± 0.22) decreased significantly post-treatment (P < 0.01). No significant change was observed in miR-132 expression. Overall, metformin modulated the expression profiles of inflammasome-related genes and miRNAs, particularly in obese patients with PCOS. Conclusion The findings suggest that metformin modulates inflammation in PCOS by altering microRNA and inflammasome-related gene expression, thereby reducing inflammatory markers such as IL-1β and miR-9, while enhancing miR-132 and miR-223, which may contribute to improved metabolic and inflammatory profiles. These results support the use of metformin as a BMI-tailored therapeutic strategy for PCOS, warranting further research to confirm its long-term effects and mechanisms.